2015
DOI: 10.1007/s00787-015-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

Child and adolescent psychiatry: which knowledge and skills do primary care physicians need to have? A survey in general practitioners and paediatricians

Abstract: Primary care physicians (PCPs) play a key role in the initial assessment and management of children and adolescents with mental health problems. However, it is unclear whether current medical education curricula sufficiently equip PCPs for this task. The aim of this study was to investigate, which child and adolescent psychiatry (CAP)-related skills and knowledge PCPs say they require in their daily practice. A questionnaire was generated, employing a modified two-step Delphi approach. Besides socio-demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 65 publications
3
24
0
2
Order By: Relevance
“…This may increase to 50% in the future given recent political pressures in the UK to increase the numbers of students going into primary care [19]. Similar conclusions are also made in a CAP curriculum review in a Canadian medical school [20] as well in several other studies examining which topics should be included in a CAP curriculum [6, 13, 21].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…This may increase to 50% in the future given recent political pressures in the UK to increase the numbers of students going into primary care [19]. Similar conclusions are also made in a CAP curriculum review in a Canadian medical school [20] as well in several other studies examining which topics should be included in a CAP curriculum [6, 13, 21].…”
Section: Introductionsupporting
confidence: 57%
“…paediatricians, have been reported to have difficulty identifying and managing psychiatric disorders presenting in CYP [24] and that newly qualified GPs feel unprepared, particularly in relation to CAP [5]. Is has been suggested that the care of CYP with psychiatric problems could be improved by adapting undergraduate education to reflect the future needs of doctors working in primary care [6]. These findings support the need for all medical students to have a foundation in Child and Adolescent Psychiatry (CAP) regardless of their future career choices [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…It allows and structures the approach, may it be in the diagnostics itself in the practice, but also for the diagnosis and, nally, in the decision whether we want and we are able to continue the treatment in the practice. (Transcription of Interview partner D14 (PAED), p. 1, lines [12][13][14][15][16] PAR and ADOL felt that their PAED allocated a large part of his consultation time to their problems. This was perceived as an indication of high quality of care.…”
Section: Metacodes and Subcodesmentioning
confidence: 99%
“…It has been argued that these referral rates are too high because even less severely affected children are referred to specialists although they would not necessarily need specialised care. Time restrictions in primary care practices as well as lack of specialised mental health training for paediatricians have been identi ed as potential reasons for constantly high referral rates (12,13). As a consequence of referral to specialized services, a number of barriers may impede or delay timely access to professional assessment and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Alexander and Heikkinen have both displayed that GPs perceive their skills in child psychiatry as somewhat inadequate [ 7 , 8 ]. The need for increased knowledge and skills among the GPs in this field is addressed several in other papers [ 3 , 9 , 11 , 13 ]. It is therefore important to gain more knowledge as to how GPs’ competence and skills can be further developed.…”
Section: Introductionmentioning
confidence: 99%